Advancements in 3D Cell Culture Systems for Personalizing Anti-Cancer Therapies - Law, Andrew M. K.; Rodriguez de la Fuente, Laura; Grundy, Thomas J.; Fang, Guocheng; Valdes-Mora, Fatima; Gallego-Ortega, David (Frontiers in Oncology, 2021)
Over 90% of potential anti-cancer drug candidates results in translational failures in clinical trials. The main reason for this failure can be attributed to the non-accurate pre-clinical models that are being currently used for drug development and in personalised therapies. To ensure that the assessment of drug efficacy and their mechanism of action have clinical translatability, the complexity of the tumour microenvironment needs to be properly modelled. 3D culture models are emerging as a powerful research tool that recapitulates in vivo characteristics. Technological advancements in this field show promising application in improving drug discovery, pre-clinical validation, and precision medicine. In this review, we discuss the significance of the tumour microenvironment and its impact on therapy success, the current developments of 3D culture, and the opportunities that advancements that in vitro technologies can provide to improve cancer therapeutics.